Reverse correlating trustworthy faces in young and older adults - Éthier-Majcher, Catherine; Joubert, Sven; Gosselin, Frédéric (Frontiers in Psychology, 2013)
Little is known about how older persons determine if someone deserves their trust or not based on their facial appearance, a process referred to as “facial trustworthiness”. In the past few years, Todorov and colleagues have argued that, in young adults, trustworthiness judgments are an extension of emotional judgments, and therefore, that trust judgments are made based on a continuum between anger and happiness (Engell, Todorov & Haxby, 2010; Todorov, 2008). Evidence from the literature on emotion processing suggest that older adults tend to be less efficient than younger adults in the recognition of negative facial expressions (Chaby & Narme, 2009; Ruffman, Henry, Livingstone et al., 2008; Firestone, Turk-Browne & Ryan, 2007; Calder, Keane, Manly et al., 2003). Based on Todorov’s theory and the fact that older adults seem to be less efficient than younger adults in identifying emotional expressions, one could expect that older individuals would have different representations of trustworthy faces and that they would use different cues than younger adults in order to make such judgments. We verified this hypothesis using a variation of Mangini and Biederman's (2004) reverse correlation method in order to test and compare classification images resulting from trustworthiness (in the context of money investment), from happiness, and from anger judgments in two groups of participants: young adults and older healthy adults. Our results show that for elderly participants, both happy and angry representations are correlated with trustworthiness judgments. However, in young adults, trustworthiness judgments are mainly correlated with happiness representations. These results suggest that young and older adults differ in their way of judging trustworthiness.